History the definitive visual guide : from the dawn of civilization to the present day - Hart-Davis, Adam (Dorling Kindersley Ltd, 2015)
Bringing the people and events of history to life, History makes the past accessible and relevant. Featuring the important events and figures that have shaped the present, from the very origins of humanity to key contemporary issues, such as the development of the internet and social media. It reveals common threads and forces that have shaped the present day. Events are set in their wider context by the comprehensive world history timeline, illuminating consequences as well as describing the moment itself. There is a focus on key profiles of major figures, exploration of important inventions and explanation of significant ideologies that defined their time. A visual celebration of human achievement and endeavour; combining fascinating content with stunning images of painting, sculpture and architecture. All of this means that a fresh and contemporary perspective is brought to the subject material. History is a dynamic encyclopaedia of world events with stunning visual impact. The story of human life is a thought-provoking and dynamic journey; a history with genes and viruses, not just battles and treaties